Investigating the Influence of Instagram Content on Self-Doubt: Implications for Psychological Well-being and Digital Literacy - Sarnoto, Ahmad Zain; Rahmawati, Sri Tuti; Sari, Windy Dian; Hidayat, Rachmat (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
This study investigates the influence of Instagram social media content on individuals' levels of self-doubt, employing a mixed-methods approach to explore the complex dynamics at play in the digital landscape. Quantitative analysis of survey data from 300 participants reveals a positive correlation between frequency of Instagram use and levels of self-doubt, with certain types of content, such as idealized lifestyles and glamorous imagery, significantly exacerbating feelings of inadequacy. Social comparison tendencies emerge as a key predictor of self-doubt, highlighting the role of perceived social norms and standards in shaping users' self-perceptions. Qualitative insights from in-depth interviews further illuminate users' subjective experiences and coping mechanisms, emphasizing the importance of digital literacy and resilience-building strategies in navigating the pressures of online environments.  The findings offer actionable implications for promoting positive mental health in the digital age, advocating for digital literacy education, and fostering supportive online communities.